SQLCM: A Contiuous Monitoring Framework for Relational Database Engines - Chaudhuri, Surajit; König, Arnd Christian; Narasayya, Vivek (20th International Conference on Data Engineering, 2004)
The ability to monitor a database server is crucial for effective database administration. Today’s commercial database systems support two basic mechanisms for monitoring: (a) obtaining a snapshot of counters to capture current state, and (b) logging events in the server to a table/file to capture history. In this paper we show that for a large class of important database administration tasks the above mechanisms are inadequate in functionality or performance. We present an infrastructure called SQLCM that enables continuous monitoring inside the database server and that has the ability to automatically take actions based on monitoring. We describe the implementation of SQLCM in Microsoft SQL Server and show how several common and important monitoring tasks can be easily specified in SQLCM. Our experimental evaluation indicates that SQLCM imposes low overhead on normal server execution end enables monitoring tasks on a production server that would be too expensive using today’s monitoring mechanisms.